The Impacts of Environment on Egg Fecundity of Thaumetopoea solitaria on different types of Trees in the North of Iraq - Omer, Muzafar K.; Hamadamin, Rawaz R. (Science Journal of University of Zakho, 2022)
In this study, egg fecundity of pistachio processionary bud moth Thaumetopoea solitaria (Lepidoptera- Notodontidae) on three different types of trees was investigated in Koya, Haybat Sultan forest during 2018 and 2019. The egg masses were collected from branches of Pistacia vera, Pistacia khunjuk and Rhus coriaria after the emergence of larvae. Collecting clusters on P. vera, P. khunjuk, and R. coriaria trees during the mentioned period was different (36 and 38, 32 and 30, and 9 and 13 respectively). In 2018, the highest ratio of eggs per mass was 159.44±15.76 on R. coriaria tree, and the lowest was 129.50±8.46 on the P. khunjuk tree. The highest percentage of the hatched egg was recorded during 2019 on P. vera tree, which was 98.41%, while 90.41%.was the lowest rate on P. khunjuk tree. Regarding the unhatched eggs, it was 96.34% on P. khunjuk tree during 2019, however, it was only 13.34% on R. coriaria in 2018. On the other hand, parasites were found to be on 42.00% of the hatched eggs on R. coriaria tree and 3.07% on P. vera tree in 2019 and 2018 respectively. Although, the ratio of the larval was ascending significantly to 96.93% on P. vera during 2018, it was descending to 58.00% on R. coriaria tree in 2019. Hence, the success of the eggs was 93.10% on P. khunjuk tree, and only 52.53% on R. coriaria in 2018. The effect of the rainfall rate during the surveyed period was considered, whilst the variation of air temperature is negligible as its effect is unnoticeable.
Keywords: Environmental Impact; Egg Fecundity; Thaumetopoea solitaria; Egg Mass; Egg Parasite; pistachio processionary bud moth; Egg parasitoid and Predator